Shape Memory Alloy – Modern Smart Material for Various Applications - Grzegorz Kłapyta (Communications - Scientific letters of the University of Zilina, 2004)
The article deals with modern materials – Shape Memory Alloys. The author presents short history of its discovery and its particular properties. One-way and two-way shape memory effects are illustrated and explained. Advantages and disadvantages of SMA are listed and possibilities of usage are discussed. There are also given some interesting applications in various fields of life illustrated by pictures and photos gathered from Internet sites.